Taxonomic status of the atherinid fish genus Melaniris in lower Central America, with the description of three new species - Bussing, William A. (1978)
Seven species of Melaniris from southern Central America are discussed, their distributions are given, and a key to their identification is provided. Melaniris guatemalensis inhabits Pacific coastal lagoons and estuaries between Guatemala and southern Costa Rica. M. beani, known only from Colón. Panamá, and M. milleri, n. sp. from Atlantic Nicaragua and Costa Rica arc principally brackish water forms, but the latter also frequents the Río San Juan basin a great distance from the sea. M. hubbsi, n. sp. occurs in the Río Escondido and San Juan drainages and is replaced in rivers to the south by M. chagresi which reaches to central Panamá. M. sardina is a lacustrine species found in several Nicaraguan lakes and in the Río Sapoá. Costa Rica. M. jiloaensis, n. sp. is endemic to Lake Jiloá, Nicaragua.